Aesthetic concrete barrier design - Bullard, D. Lance (Delbert Lance) (Report (National Cooperative Highway Research Program), 2006)
"TRB's National Cooperative Highway Research Program (NCHRP) Report 554: Aesthetic Concrete Barrier Design provides guidance for the aesthetic treatment of concrete safety shape barriers"--Publisher's description